2019
DOI: 10.1039/c8ta11948a
|View full text |Cite
|
Sign up to set email alerts
|

Coordination derived stable Ni–Co MOFs for foldable all-solid-state supercapacitors with high specific energy

Abstract: Coordination derived stable Ni–Co MOF (833 F g−1) based foldable all-solid-state supercapacitors show a high specific energy of 77.7 W h kg−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(65 citation statements)
references
References 55 publications
1
64
0
Order By: Relevance
“…The broad bands at 3483 cm −1 and 2857 cm −1 , which are found only in Ni/Co-MOF are atrributed to the presence of hydroxyl groups and CH stretching vibration respectively [24]. Two strong bands at ∼1629 and ∼1286 cm −1 were assigned to the asymmetric and symmetric stretching modes of the coordinated (COO-) group respectively [28].…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 95%
See 1 more Smart Citation
“…The broad bands at 3483 cm −1 and 2857 cm −1 , which are found only in Ni/Co-MOF are atrributed to the presence of hydroxyl groups and CH stretching vibration respectively [24]. Two strong bands at ∼1629 and ∼1286 cm −1 were assigned to the asymmetric and symmetric stretching modes of the coordinated (COO-) group respectively [28].…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 95%
“…The peak at 1286 cm −1 is also ascribed to the stretching vibration of C-O bond in the uncoordinated free carboxyl on the surface of the MOFs [29]. The band at 636 cm −1 was attributed to the stretching vibrations of para-aromatic CH groups and δ-OH [28]. The separated bands between the asymmetric and symmetric stretching modes indicate that, -COOof trimesic acid is coordinated to Ni 2+ or Co 2+ or Ni 2+/ Co 2+ via a bidentate ligand mode and the (BDC) 3metallic exhibits a polymeric structure [20].…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 96%
“…Emerging as a new category of crystalline porous materials with ultrahigh porosity and abundant metal active sites, metal-organic frameworks (MOFs) are assembled by the coordination bond between metal ions and organic ligands, giving the enormous application prospects [20][21][22]. Recently, extensive researches related to transition metal-based MOFs have been demonstrated that they are the appealing candidates for energy conversion and storage [23][24][25]. However, most MOFs electrodes unavoidably suffer from inherently low electrical conductivity and instability, which has greatly thwarted their capacitive performances and rate capacities [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The specific capacitance of 1.0-3# composite electrode retains 83.9 % of its original capacitance (571 F g À 1 ) when the current density is 10 A g À 1 (Figure 6c). Furthermore, EIS confirms the fast ion diffusion process of 1.0-3# composite electrode ( Figure S7) [48,49] . Figure 6d shows the capacity retention of all electrodes after 1000 cycles at a current density of 10 A g À 1 .…”
Section: Resultsmentioning
confidence: 64%